Jaringan Kerja Sama Perpustakaan di Indonesia - Chintya Almira; Yusniah Yusniah (Comit: Communication, Information and Technology Journal, 2023)
Domestic library cooperation network is intended as a type of network that occurs in libraries so that cooperative relationships between other libraries are established in an effort to fulfill what is needed by users so that they can satisfy users and the purpose of library services can be achieved. The method used to carry out this research is to conduct a literature study which is further developed in a qualitative descriptive form so that the contents of the journal will provide a more in-depth explanation. The results of the study explain that it is necessary to implement a collaboration network between libraries in either conventional or digital form. Keywords: network, cooperation, library